Impacto do uso de coleiras impregnadas com deltametrina a 4% na prevenção da leishmaniose visceral canina, no município de Juatuba, Minas Gerais. - Sara Clemente Paulino Ferreira e Silva (2017)
Visceral leishmaniasis (VL) is an important zoonosis in Public Health, especially in developing countries. The adopted measures for its prevention and control are controversial and the real impact caused by them is questionable. The aim of this study was to evaluate the efficacy of using deltamethrin-impregnated dog collars in the prevention and control of canine VL (CVL) in a municipality of Minas Gerais, Brazil. An epidemiological intervention study was conducted by comparing morbidity measures (prevalence and person-time incidence) in two distinct areas: the first one the Experimental Area (AE), where the proposed measure was implemented, and the second one the Control Area (CA). In both areas blood samples were collected from dogs. In the EA the animals also received collars impregnated with deltamethrin 4%. For diagnosing the animals, two serological tests were used in series: a rapid test (TR-DPP) as triage, and an enzyme-linked immunosorbent assay (ELISA) as confirmatory, as preconized by Brazils Ministry of Health. Six months after the first visit, a second blood sample was taken from the animals, in order to determine the incidence of LVC, the relative risk and the efficacy of the intervention. In the first intervention, 1020 dogs from the EA, and 589 from the CA were examined. The prevalence calculated for the EA was 4,41% (CI95% 3,27-5,91), and for the CA was 7,13% (CI95% 5,25-9,59). The odds of infection observed, 1,6636 (CI95% 1,08-2,57), indicated that dogs from the CA had naturally more chances of infecting with VL than dogs from the EA. In the second intervention, 454 dogs from the EA, and 292 from the CA were examined. The person-time incidence observed in the EA was 3,51% (CI95% 1,30-7,48), and in the CA was 5,82% (IC95% 3,43-9,16). Due to the difference found in the odds of infection, a correction in the number of the new cases from CA was made by maintaining 66% (n = 17) of them, and the new person-time incidence value found was 11,81% (CI95% 7,03-18,23). The difference between the calculated incidences was statistically significant (p=0,009). The relative risk value found was 0,2972 (CI95% 0,1204-0,7339; p=0,009), which demonstrated that the proposed measure was a protection factor, and the efficacy of the mass use of collars was estimated in 70,27%. A high rate of collar losses was observed in this intervention, 40,96% (186/454) of the dogs were not using them. However, despite of the collar losses, the proposed measure protected the dogs of the EA 3,36 more times from becoming seropositive. These results give scientific based evidence that the mass use of insecticide-impregnated dog collars is an alternative to be considered in the combat against CVL.